A Survey on Network Intrusion System Attacks Classification Using Machine Learning Techniques. Issue 1 (January 2021) - Deepa, V.; Radha, N.
Abstract: Wireless Local Area Network (WLAN) security management is now being confronted by rapid expansion in wireless network errors, flaws and assaults. In recent times, as computers are used extensively through network and application creation on numerous platforms, attention is provided to network security. This definition includes security vulnerabilities in both complicated and costly operating programs. Intrusion is also seen as a method of breaching security, completeness and availability. Intrusion Detection System (IDS) is an essential method for the identification of network security vulnerabilities and abnormalities. A variety of significant work has been carried out on intrusion detection technologies often seen as premature not as a complete method for countering intrusion. It has also become a most challenging and priority tasks for security experts and network administrators. Hence, it cannot be replaced by more secure systems. Data mining used for IDS can effectively identify intrusion and the identified intrusion values are used to predict further intrusion in future. This paper presents a detailed review of literature about how data mining techniques were utilized for intrusion detection. First, intrusion detection on various benchmark and real-time datasets by data mining techniques are studied in detail. Then, comparative study is conducted with their merits and demerits for identifying the challenges in those techniques and then this paper is concluded with suggestions of solutions for enhancing the efficiency of intrusion detection in the network.